Digital smile design (DSD): reprodutibilidade e influência do planejamento estético do sorriso para obtenção do enceramento diagnóstico - Tolentino, Katieny Lacerda (2018)
Technological advances with digital methods have been contributing to the construction of esthetic planning of smileand one of these methods is the Digital Smile Design (DSD). This study aims to evaluate the reproducibility of digital planning with the DSD method and its influence in obtaining the diagnostic wax-up performed by the dental prosthesis technician. The methodology was subdivided into three stages: 1- Elaboration, by the research team, of a protocol with instructions to carry out a digital smile planning of ten patients. The protocol, the study model and the photographs from the patient were sent to 10 dentists to prepare the digital planning for each case; 2- Making a diagnosis wax-up with DSD and another one without DSD by the dental prosthesis technician, to each one of the patients; 3- Execution of digital planning by the dentists. All statistical tests were performed at a significance level of 5% with SPSS software for Windows 25.0 (IBM, USA). The DSD method was reproducible by dentists (p <0.05, ICC higher than 0.4). Not all the dental prosthesis technicians reproduced, in the wax-up models with the aid of DSD, the guidelines provided by the digital planning, differing in models width (p = 0.01). There were differences between the diagnostic wax-up models obtained with and without the DSD guidelines. The wax-up models without DSD had higher incisal increases (p = 0.048).